STATUS KESEHATAN BAYI DAN SIKAP PETUGAS TERHADAP PELAKSANAAN (IMD) PADA IBU BERSALIN - Nurmaliza mali liza; Nurmaliza Nurmaliza (Universitas Harapan Bangsa Purwokerto, 2018)
Early breastfeeding initiation (IMD) is a natural process of returning a baby to breastfeed, by allowing the baby to seek and suck his own milk. Survey of WHO through more than 3000 post-partum maternal in each states, show that the maternals which operate IMD or giving of the breastfood minimally a hour after the baby is born only about 38,33%. IMD scope in Indonesia is still low, those are 29,3% in 2010 experiences the decrease to be 34,5% in 2013. The IMD practice proporsion in a hour early birth is 43,9%, while IMD in a early day is 61,5%. The research aims to determine the factors which relate with the early breastfood initiation operation, that is the medical worker’s attitude and baby health status. The research is analytic quantitaive with design type is cross sectional. The data analysist was operated as univariate and bivariate Population is all post-partum maternals which was in he maternity hospital of society health center working area of Payung Sekaki of Pekanbaru city in 2015 with 220 people. The used sampling method is proportional sampling. The result of bivariate analysis showed that there was correlation between infant health status and health officer attitude toward IMD implementation with p-value <0.05 (<0.001 <0.05). Suggested on the maternals and medical workers to operate and support the early breastfood initation program, then decreasing the nutrient as long as the pragnance to avoid abnormality or disturbion on the baby.